Magnetic navigation and actuation of nanorobotic systems through the use of Helmholtz coils - Nunes, Daniel Filipe Vilhena (2019)
Tese de mestrado em Física, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, em 2018